Extraction of fatty acids and cellulose from the biomass of algae Durvillaea antarctica and Ulva lactuca: An alternative for biorefineries - Valerio Filho, Alaor; Santana, Luiza Ribeiro; Motta, Naiane Garcia; Passos, Luan Ferreira; Wolke, Silvana Ines; Mansilla Muñoz, Andres Omar; Astorga España, Maria Soledad; Becker, Emilene Mendes; Pereira de Pereira, Claudio Martin; Villarreal Carreno, Neftali Lenin (My University, 2023)
Algae have cellular structures, rich in polysaccharides, proteins, lipids, vitamins and minerals. In addition, fatty acids are known for their benefits to human health, such as in treating blood pressure, diabetes, and obesity. These properties determine the algal biomass value as a raw material for different applications. One of the polysaccharides present in algae and is still little explored is cellulose, an important material for numerous technological applications. In this study, Durvillaea antarctica and Ulva lactuca algae were used as raw materials for the production of a cellulosic-based materials combining alkaline treatment, bleaching and freeze-drying. The samples were analyzed by XRD,13C-CP-MAS-NMR, FT-IR, SEM, TEM and TGA techniques. XRD analysis showed that the material obtained presented crystallinity of above 60 %. FT-IR revealed that the methodology was effective in obtaining cellulose. SEM and TEM images exhibited a morphology consisted of cellulose fibers.
Keywords: seaweed; sub-antarctic chilean algae; ultrafine fiber; lipids